Anti-proliferative potential of cyclotetrapeptides from Bacillus velezensis RA5401 and their molecular docking on G-Protein-Coupled Receptors. (October 2018) - Rehman, Najeeb Ur; Abed, Raeid M.M.; Hussain, Hidayat; Khan, Husain Yar; Khan, Ajmal; Khan, Abdul L.; Ali, Majid; Al-Nasri, Abdullah; Al-Harrasi, Khalid; Al-Rawahi, Ahmed N.; Wadood, Abdul; Al-Rawahi, Ahmed; et al.
Abstract: Elucidation of bioactive chemical compounds from rhizobacteria is highly utilized in pharmaceuticals and naturopathy, due to their health benefits to human and plants. In current study, four cyclopeptides along with one phenyl amide were isolated from the ethyl acetate extract of Bacillus velezensis sp. RA5401. Their structures were determined and characterized as cycle (L-prolyl-L-leucyl)2 (1 ), cyclo (L-prolyl-l -valine)2 (2 ), cycle (L-phenylanalyl-L-propyl)2 (3 ), cyclo (D-pro-L-tyr-L-pro-L-tyr)2 (4 ) and N-(2-phenylethyl)acetamide (5 ) on the basis of electron spray ionization mass spectrometry (ESI-MS), nuclear magnetic resonance (NMR) techniques and comparison with the literature data. The five compounds have been isolated for the first time from this species. The effect of various concentrations of these compounds on the proliferation of MDA-MB-231 breast cancer cells was examined. It was found that1 and2 induced concentration-independent anti-proliferative effects, while3, 4 and5 inhibited cancer cell proliferation in a concentration-dependent manner. Furthermore, to determine the suitable binding targets of these compounds within cancer cell line, detailed target prediction and comparative molecular-docking studies were performed. The compounds1 and2 hit intracellular anti-cancer targets of proteases family, while compounds3, 4 and5 interacted with different membrane receptors of G-Protein-Coupled Receptors (GPCRs). In conclusion, the Bacillus velezensis RA5401 can be an ideal strain to produce anti-proliferative constituents at industrial scale. Highlights: First report on the isolation of cyclotetrapetides from Bacillus velezensis strain. Three compounds (3, 4 and5) inhibited cancer cell proliferation in a concentration-dependent manner. Bacillus velezensis can be an ideal strain to produce anti-proliferative constituents at industrial scale. In silico docking study of the compounds displayed possible mode of action in a hypothetical way.